2020
DOI: 10.2169/internalmedicine.6083-15
|View full text |Cite
|
Sign up to set email alerts
|

Infective Endocarditis with No Underlying Disease for Which Bacterial Endophthalmitis Have Been the First Symptom

Abstract: Bacterial endophthalmitis is a rare complication of infective endocarditis (IE). We herein report a case of IE with no underlying disease for which endophthalmitis could have been the first symptom. A 58-year-old man was admitted to our hospital with a fever, vision disturbances, and pain in the left hand joint. His left eye was removed because fusion on the cornea progressed. Streptococcus agalactiae was detected in blood cultures, fluid cultures from his left hand joint, and the remove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…EE is rarely the first symptom of endocarditis, as it usually indicates a developed infection that is difficult to overlook or ignore, but such cases have been reported [ 28 , 31 ]. As endocarditis is a common cause of EE, a transesophageal echocardiogram should be performed in any patient with an unknown source of infection and suspected heart failure.…”
Section: Primary Source Of Infectionmentioning
confidence: 99%
“…EE is rarely the first symptom of endocarditis, as it usually indicates a developed infection that is difficult to overlook or ignore, but such cases have been reported [ 28 , 31 ]. As endocarditis is a common cause of EE, a transesophageal echocardiogram should be performed in any patient with an unknown source of infection and suspected heart failure.…”
Section: Primary Source Of Infectionmentioning
confidence: 99%
“…Additionally, several case reports have shown that AS patients develop endophthalmitis as a complication of systemic infection (19,20). Furthermore, previous case reports also demonstrated the relation between endophthalmitis and cardiovascular diseases, such as myocarditis and endocarditis (21)(22)(23). However, data regarding the prevalence of endophthalmitis in AS patients are scarce.…”
Section: Introductionmentioning
confidence: 99%